Variable resolution modeling of near future mean temperature changes in the dry sub-humid region of Ghana (2018)
The study used two models from Rossby Centre Regional Atmospheric Model (RCA4) and two from Weather Research and Forecasting Model (WRF) plus the Statistical Downscaling Model—Decision Centric (SDSM-DC) at 44 km, 12 km and 2 m resolution respectively to project the impact of climate change on mean temperature in the Pra River Basin for the period 2020–2049. Results showed that the minimum temperature increased (+ 1.47 °C) faster than the increase (+ 1.11 °C) in maximum temperature for observed period 1981–2010. An evaluation of the performance of the models with time-series based metrics showed that SDSM-DC and RCA4 are better for projecting mean temperature in the study area compared to WRF despite its resolution. Analysis of variance (p < 0.05) indicated significant difference between the projected mean temperature of the five models but there was no significant difference between SDSM-DC and RCA4 models. Correlation between models was highest at R = 0.727 between SDSM-DC and RCA4. The years 2041, 2042 and 2047 were projected as hottest by minimum two different models. The mean temperature change was projected at + 1.36, + 1.42 and + 1.12 °C by SDSM-DC, RCA4 and WRF respectively. The ensemble of projection depicted same trend of February—April as the high mean temperature and July—September as the lowest as was for the observed period. However, January is projected to have the highest change in mean temperature of + 1.51 °C. The maximum temperature for observed period was found to be the mean temperature in the period 2020–2049. Future study will focus on the impact of projected temperature change on ecosystem services delivery in the region.